Beberapa ukuran antropometri pada atlet sepakbola dan bulutangkis di Yogyakarta - Neni Trilusiana Rahmawati, Neni Trilusiana Rahmawati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1996)
A study on some anthropometry measurements of soccer and badminton athletes in Yogyakarta had been done. The objective of the study was to investigate the differences of anthropometry measurements for different types of sport on soccer and badminton athletes in Yogyakarta.The subjects of the study consisted of 20 soccer players and 20 badminton players, with the age of 17 - 25 years. The t-test was used to know the differences of anthropometry measurements between soccer and badminton players.The results indicated that the average height, body weight, sitting height, biiliocristal breadth, upper arm and thigh girth of soccer players were significantly greater than those of badminton players. The biacromial breadth, calf girth, arm and total leg length between the two sport groups were not significantly different. There were somatotype differences between soccer and badminton players, and the major difference in the distribution of the two samples was that the soccer players were less endomorphic and ectomorphic than the badminton players.Further studies may explain those results with more consideration on different types of exercise performed by more samples.Key words: sport anthropology - soccer & badminton athletes - anthropometry somatotype bodymeasurements